The Female Consort as Intercessor in Sixteenth-Century Saxony - Arenfeldt, Pernille (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
During the past ten to fifteen years the research interest in queens, female regents and consorts has grown rapidly. Continuing the approach advocated by gender and court historians alike, the analyses of women at the early modern courts have generally focused on informal forms of power. Although the increased emphasis on informal power has proved immensely productive in many respects, it has also resulted in oversimplifications and misleading anal-ogies; for example, in one study the agency of the female consort is reduced to a function of her marital relation and another historian concludes that the position of the female consort resem-bled that of the maîtresse or the court favorite. These conclusions also represent a conceptual – and highly political – problem because power is defined as access to the ruler. This implies that the ruler and other decision-makers are viewed as the “real” authorities. Unwittingly, the narrow view of politics and authority that gender historians persistently have striven to chal-lenge is thereby reconfirmed.